Letter - Tomás, Pascual, 1893-1972
026-0073-001 Pascual Tomas Diputado Rue du Taur 69 TOULOUSE. Toulouse June 7th. 1939. PRIVATE AND CONFIDENTIAL Sir Walter Citrine London. My Dear Friend, Just received by the mean of a friend of mine, a letter from my wife, in which she tells me that her present address is: ALFAFAR. Valencia. Calle de Calvo Sotelo. 25. My wife and daughters situation's is actually desperate they cannot go out from the house where they are hiding, fearing always to be detained by the Police. I must also tell you, dear Citrine, that the nationalists took everything we had in our apartments in Madrid and in Valencia, my wife and daughters haven't any economic means, and they are only living on charity. With all my friendship feelings for you, I beg you to tell me if there is any possibilities through the English Consul in Valencia to get in touch with my wife and give her the few pesetas that she needs to live till the moment you can take them away from Spain. I don't have to tell you that the contact with her has to be made with much reserves. Thanking you for all what you have done and you still doing for me, I'm Dear friend, very sincerely yours. Pascual Tomàs 292/946/26/73